A Space with a Lusin $π$-Base Whose Square Has No Lusin $π$-Base - Patrakeev, Mikhail (Topology Proceedings, 2021)
We construct a space $X$ that has a Lusin $π$-base and such that $X^2$ has no Lusin $π$-base.